1989
DOI: 10.1117/12.948894
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Integrated Fiber Optic Damage Assessment System For Composite Materials

Abstract: Progress toward the development of a fiber optic damage assessment system for composite materials is reported.This system, which is based on the fracture of embedded optical fibers, has been characterized with respect to the orientation and location of the optical fibers in the composite.Together with a special treatment, these parameters have been tailored to yield a system capable of detecting the threshold of damage for various impacted Kevlar /epoxy panels.The technique has been extended to measure the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
1
16
1
Order By: Relevance
“…This in tum depends upon the overall layup and the direction of the applied load. This observation is consistent with our understanding that through-the-thickness matrix cracks constitute the principal fracture mechanism for embedded optical fibers [8]. In general the optical fibers should be perpendicular to the reinforcing fibers in the ply that separates the optical fibers from the region of damage to be sensed.…”
Section: Treatment Orientation Depth and Influence Of Embedded Optisupporting
confidence: 77%
See 4 more Smart Citations
“…This in tum depends upon the overall layup and the direction of the applied load. This observation is consistent with our understanding that through-the-thickness matrix cracks constitute the principal fracture mechanism for embedded optical fibers [8]. In general the optical fibers should be perpendicular to the reinforcing fibers in the ply that separates the optical fibers from the region of damage to be sensed.…”
Section: Treatment Orientation Depth and Influence Of Embedded Optisupporting
confidence: 77%
“…The simplest form of such a system would involve the interrogation of the optical fibers by a source of light and disruption in their transmission due to their fracture used to determine the location and extent of damage. We have undertaken extensive measurements to demonstrate the viability of employing imbedded optical fibers for assessing impact induced damage in Kevlar/epoxy samples [8,9]. We have also shown that load induced growth of a damage zone resulting from fatigue, mishandling, excessive load or flaws created during manufacture could also be detected by this system [ 10].…”
Section: Merits Of An Optical Fiber Based Systemmentioning
confidence: 99%
See 3 more Smart Citations